Buffel grass provides a valuable option to restore degraded rangelands and forage for livestock in Tanzania - Louhaichi, Mounir (International Center for Agricultural Research in the Dry Areas, 2024)
The image depicts cows grazing on Cenchrus ciliaris in Tanzania.